Wordsworth's Sense of Place : Assimilation or Dominion - Domines Veliki, Martina (2010)
Poststructuralist and New Historicist readings of Wordsworth's poetry prioritize the mind of the poet over the material world that surrounds him, and they speak of the poet’s dominion over the external world. Nature becomes a mere linguistic construct serving as a vehicle for something else: the hegemony of imagination (in the case of Hartman and Bloom) or the mind’s denial of history (called ‘romantic ideology’in the New Historicist readings). This paper wants to explore ecocritical and phenomenological possibilities of reading Wordsworth's poetry remembering primarily that Wordsworth was a pedestrian poet with deep awareness of the sustaining power of his surroundings and of the need to preserve the spot and the land. Nature in such poems as Home at Grasmere, The Thorn, Poems on the Naming of Places is first and foremost Wordsworth’s reality: it does not only exist as signified within human culture. What the poet manifests in these poems is his localness, rootedness, his knowing of a particular place, his self-conscious relation to the place. He does not speak about any nature, but nature ‘then’ and ‘there’, nature of that particular time and at that particular place.
Projekt MZOS
ENG